Effects of Foreign Direct Investment (FDI) and Economic Growth on Employment and Female Employment in Nigeria (2006-2019) - Ahmed Sani, Idris; Omodadepo Adebiyi, Oyeyemi (Kashere Journal of Humanities, Management and Social Sciences, 2022)
Despite the fact that Nigeria is ranked the third host economy for FDI behind Egypt and Ethiopia in 2019, FDI growth rate does not often result to employment creation in the country. The country has witnessed a persistent unemployment which has been a major macroeconomics issue of Nigeria since her independence. Therefore, this study analysed the effects of FDI and economic growth on employment and female employment in Nigeria using quarterly data for the period 2006:Q1 to 2019:Q4. The study employed the Dynamic Ordinary Least Squares (DOLS) as its technique of analysis. Contrary to the theoretical expectations, the results of co-integration coefficients asserted that foreign direct investments negatively affect employment and female employment in Nigeria. Nevertheless, the findings of the study further revealed that economic growth affect employment and female employment positively. This is found to be in line with theoretical expectations of the research. The study recommended that Nigerian government should enact policies that will encourage female folk to be more visible and active in the assessment of FDI inflow resources and subsequent investment. This can be achieved through government desire to come up with policies that will maintain a certain percentage of FDI inflows for the female folk. Furthermore, female gender should be encouraged to form groups that can serve as catalyst for female gender involvement in employment and FDI resources assessment.